Effectiveness of the Preparation of the Regional Governance Implementation Report (LPPD) Through Coordination Among Regional Apparatuses in Tangerang Regency in 2023 - Muhammad Fariz Iqbal; Muhadam Labolo; A. Masrich (Sean Institute, 2026)
The preparation of the Regional Government Implementation Report (LPPD) is a constitutional obligation of regional heads as a form of accountability for government administration to the central government and society. This study aims to analyze the effectiveness of LPPD preparation through coordination among regional apparatus in Tangerang Regency in 2023, identify inhibiting factors, and describe efforts made to improve preparation effectiveness. The research uses a qualitative approach with a descriptive design, with data collection techniques through in-depth interviews, observation, and documentation studies. Research informants consist of the Regional Secretary, Head of Government Administration Section, representatives from the Inspectorate, Regional Planning and Development Agency, Population and Civil Registration Office, and staff of the Government Administration Section selected using purposive sampling and snowball sampling techniques. Data analysis was conducted using Duncan's effectiveness theory which includes three dimensions: goal attainment, integration, and adaptation. The research results show that the implementation of LPPD preparation in Tangerang Regency in 2023 has generally not been effective. In the goal attainment dimension, delays in data submission from most regional apparatus were found, with only four apparatus completing data on the first request letter. In the integration dimension, coordination and communication among regional apparatus are still weak, evident from slow responses to data requests and ineffective communication through WhatsApp groups. In the adaptation dimension, there are still obstacles in using the SiLPPD application and limited human resources who understand technical guidelines. Inhibiting factors include delays in data submission, weak coordination and communication, absence of reward and punishment systems, limited human resources, and technical obstacles in using the SiLPPD application. Efforts to improve effectiveness are carried out through strengthening coordination among regional apparatus, increasing supervision and evaluation, implementing coaching clinics, and applying parallel validation by the Inspectorate. This research concludes that although there have been improvement efforts, the effectiveness of LPPD preparation still requires strengthening through the formation of a permanent LPPD Coordination Team, comprehensive SOP development, establishment of clear reward and punishment systems, and continuous human resource capacity building.